Strip planted mechanical seeding of mustard and mungbean with crop residue retention is more profitable than conventional practice - M. M. Hossain; M. Begum; M. M. Rahman (Future Science, 2021)
Smallholder agriculture of the Asian continent faces a significant challenge of declining soil productivity and an acute shortage of agricultural labor. Reduced tillage and crop residue mulch application is an integrated approach to preserving soil health and addressing the labor crisis to maintain farm sustainability. We undertook this study to evaluate the effect of strip planting and increased residue mulching on mustard and mungbean's productivity and profitability in northern Bangladesh during 2015 and 2016. Mustard cv. BARI Sharisha 14 and mungbean cv. BARI Mungbean 6 was grown following (i) Conventionally Tilled broadcasting method (CT) and (ii) Strip Planted line seeding (SP) with two levels of crop mulch (i) no-mulch and (ii) 50% mulch. The CT was done by a two-wheel tractor with four plowings and cross plowing followed by leveling. In SP, single tillage, seeding, fertigation, and field leveling were done simultaneously by a Versatile Multi-crop Planter machine. Results reveal that mechanized seeding of mustard and mungbean in SP with 50% residue mulching fetched 62% higher profit than broadcasted CT without residue through producing 24% higher seed yield. This practice reduced the land preparation costs by 68%, in association with reducing the labor and fuel requirements by 30%. Hence, it could be concluded that the mechanized seeding of mustard and mungbean with the retention of 50% of crop residue is profitable to the conventionally broadcasted seeding process.